Pieces - Lynch, Chris, 1962- (Simon & Schuster BFYR, 2013)
Eighteen-year-old Eric deals with the loss of his older brother Duane by meeting three of the seven recipients of Duane's organs a year after his death, and pondering who they are to him, and he to them.